Parapsyche species (Trichoptera: Hydropsychidae: Arctopsychinae) of western North America - Givens, Donald R. (Zootaxa, 2015)
The adult female, pupa, and larva of the 5 western North American species of the arctopsychine genus Parapsyche—P. almota Ross 1938, P. elsis Milne 1936, P. extensa Denning 1949a, P. spinata Denning 1949b, and P. turbinata Schmid 1968—are reviewed. The female and larva of P. extensa are described for the first time. The larvae of P. spinata and P. turbinata are described for the first time. The chaetotaxy of the larval forms of western North American Parapsyche is discussed and scanning electron micrographs are presented. Keys to the females, known pupae, and larvae are provided. Distributional and biological data are also included.